UJI SIFAT SENSORIS DAN AKTIVITAS ANTIOKSIDAN KOLANG-KALING DENGAN PENAMBAHAN EKSTRAK KAYU SECANG (Caesalpinia sappan L.) SEBAGAI PEWARNA ALAMI - Thoyibi, Dhimas Ridwan; Duniaji, Agus Selamet; Suter, I Ketut (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 4 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i04.p03, 2019)
This study purpose to determine the effect of added sappan wood extract to be sugar palm fruit natural colored toward characteristic sensory evaluation, activities of antioxidant, and to know the best concentrate of sappan wood extract with higgest characteristic sensory and antioxidant. The research design was used Completely Randomize Design with 6 treated exctract concentrating which is 0% ; 2% ;  4% ; 6% ; 8% ; 10%. The treatment was repeated three times so that have 18 unit experimental. Data were analyzed by Analysis of  Variance (ANOVA) and then continued with Duncan Multiple Range Test (DMRT). Result of this shown that the extract concentrate have very significant effect towards activities antioxidant, and anthocyanin levels. Have significant effect towards color (hedonic test). Has not significant effect towards flavour, taste, and overall acceptance (hedonic test). Concentrate 10% was the best treatment for produce sugar palm fruit with characteristic sensory color (liked), taste (rather liked), flavour (liked) and overall acceptance (rather liked), the highest value of  antioxidant activitiest (based on IC50) 169.65 mg/ml, and anthocyanin 0.40 mg/100g. Keywords : sappan wood, sugar palm fruit, extraction, natural colored, antioxidant activity.